Energy optimization in integrated pulp and paper mills with recourse to environmental benefits - Pharande, V. A.; Asthana, S. R.; Saini, D. R.; Kaul, S. N. (Journal of Scientific & Industrial Research, 2011)
This study focuses on energy optimization in evaporator and digester of integrated pulp and paper mills in India, and recommends application of 7 effects/plates evaporator in place of 5 effects/plates normally used. Steam economy resulting from this modification is definitely more than 7. Pinch technology is found suitable for optimization of controlled parameters in the digester. Using recommendations, total energy savings was observed in West Coast Paper Mill (11.74%) and Star Paper Mill (12.97%). Environmental benefits that will accrue in terms of reductions in emissions are: SPM, 46464-48664 TPA; SO(2), 1045 kg/annum; H(2)S, 55,020 kg/annum; and CO(2), 13612 TPA.
Keywords: Air emissions; Digester; Evaporator; Pinch technology; Steam economy